F-supplemented modules - Özdemir, S. (Algebra and Discrete Mathematics, 2020)
Let R be a ring, let M be a left R-module, and let U, V, F be submodules of M with F proper. We call V an F-supplement of U in M if V is minimal in the set F ⊆ X ⊆ M such that U+X = M, or equivalently, F ⊆ V , U+V = M and U∩V is F-small in V . If every submodule of M has an F-supplement, then we call M an F-supplemented module. In this paper, we introduce and investigate F-supplement submodules and (amply) F-supplemented modules. We give some properties of these modules, and characterize finitely generated (amply) F-supplemented modules in terms of their certain submodules.